Strategi Bisnis pada PT Wirapati Garuda Paksi - Astini, Rina; Adhiprasetyo, Rizcky (Bina Nusantara University, 2010)
PT Garuda Wirapati Paksi (WGP) is a private corporation engaged in the Security and Rescue Services Business Sector (BUJPP) in guarding. Many challenges arise from the external environment such as unstable political and economic conditions, competition among companies and the entry of foreign firms. To face the above phenomenon, the right and effective business strategy is the right tool for avoiding the challenge. Business strategy planning is absolutely necessary for companies that want to survive in the future. The research method is descriptive. Data collection techniques used are questionnaire and interview with relevant parties within the company. The data have been obtained that, in the analysis through three phases, namely input, matching, and decision stage. The final results of this study concluded that the proposed effective business strategy for PT Garuda Wirapati Paksi based on QSPM matrix is Market Penetration Strategy. This strategy is considered to reduce business risk arising as a result of significant changes to the external environment of the company.